Mendorong Ekonomi Lokal melalui Unit Usaha WEIPA: Peran Inovasi Pesantren - Saibil, Defi; Haq, Furqonul (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: The community service activities (PKM)  is a qualitative study with a descriptive approach aimed at increasing the efficiency of business units in WEIPA, particularly in the culinary, fashion, and batik units. Methodology: Data was collected through observation and interviews. Results: The management of each business unit begins with the preparation stage and processes directed towards achieving the desired results. Conclusions: Al-Mumtaz Islamic Boarding School plays a significant role in improving the local community's economy through various business units they manage, such as catering, fashion/clothing, and batik. The pesantren helps the surrounding community become more economically independent by providing skills training and entrepreneurship programs. Additionally, the WEIPA business unit within the pesantren implements various best practices. The training and empowerment provided to students and the local community enhance their skills and productivity, making Al-Mumtaz Islamic Boarding School an effective driver of the local economy while continuing to fulfill its role as a center for religious education. Limitations: The community service activities (PKM) have several weaknesses, causing Al-Mumtaz (WEIPA), which has high-quality equipment and machinery, to encounter problems due to the crew's lack of knowledge in their use and maintenance. Contribution: Increasing crew knowledge and skills through the recruitment of experts and regular training, strengthening management with clear institutionalization, focusing on skill enhancement and the development of pesantren economic business units, conducting comparative studies to improve product competitiveness, and continuous evaluation and supervision to ensure effective and efficient resource utilization.